2011
DOI: 10.3892/ijo.2011.1087
|View full text |Cite
|
Sign up to set email alerts
|

Statins induce apoptosis and inhibit proliferation in cholangiocarcinoma cells

Abstract: Abstract. Given the poor prognosis for cholangiocarcinoma, new and effective treatments are urgently needed. HMG-CoA reductase inhibitors (statins) reportedly exert anticancer effects in a variety of diseases, but there have been no reports of these effects in cholangiocarcinoma. In this study, we investigated the utility of statins for cholangiocarcinoma treatment. Proliferation suppression by pitavastatin and atorvastatin was investigated in the human cholangiocarcinoma cell lines HuCCT1 and YSCCC while chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…In prostate cancer cells, the two apoptotic pathways are activated by the action of lovastatin and simvastatin, although it seems that the main route is the extrinsic one (52). In cholangiocarcinoma cells treated with pitavastatin and atorvastatin, apoptotic processes by the pathway dependent on mitogen-activated protein kinase (MAPKs) have also been identified (53). In breast cancer cells, some studies have detected the potential antiproliferative effects by statins inducing apoptosis (54).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cells, the two apoptotic pathways are activated by the action of lovastatin and simvastatin, although it seems that the main route is the extrinsic one (52). In cholangiocarcinoma cells treated with pitavastatin and atorvastatin, apoptotic processes by the pathway dependent on mitogen-activated protein kinase (MAPKs) have also been identified (53). In breast cancer cells, some studies have detected the potential antiproliferative effects by statins inducing apoptosis (54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, statins perform roles in immune regulation (11), the inhibition of inflammation (12) and the modulation of angiogenesis (13). Statins also exhibit anticancer activities (14,15), decrease cellular proliferation (15)(16)(17) and induce apoptosis (15,18,19) in breast, colorectal, lung, prostate and pancreatic cancer (20). Notably, statins inhibit cancer cell growth in vivo and decrease metastasis at clinically therapeutic doses (21).…”
Section: Introductionmentioning
confidence: 99%
“…Reliable evidence from in vitro and in vivo data has demonstrated that statins exert pleiotropic actions beyond their lipid-lowering effects, including in cancer prevention and treatment (6,18). Previous studies have also reported that statins trigger cancer cell apoptosis in various cancer cell types (19,20). The results from the present study revealed that short-time use of low-dose simvastatin had a very limited effect in inhibiting cell viability and inducing cell apoptosis at 24 h following treatment.…”
Section: Discussionmentioning
confidence: 85%